Implementation strategies for the introduction of the RTS,S/AS01 (RTS,S) malaria vaccine in countries with areas of highly seasonal transmission: workshop meeting report - Corinne S. Merle; RTSS-SMC working group (Malaria Journal, 2023)
Abstract A workshop on implementation strategies for the introduction of the RTS,S/AS01 (RTS,S) malaria vaccine in countries with areas of highly seasonal transmission, was held as a hybrid meeting in Dakar, Senegal, and online, 23–25 January 2023. Delegates from Expanded Programmes on Immunization (EPI) and National Malaria Control Programmes (NMCPs) from 13 African countries, and representatives from key stakeholders participated. RTS,S is the first malaria vaccine to be recommended by the World Health Organization (WHO). The recommendation followed pilot implementation of the vaccine in Ghana, Kenya and Malawi, which showed that introduction of the vaccine was highly effective at scale, and was associated with a 30% reduction in hospital admissions with severe malaria in age groups eligible to have received the vaccine and no evidence of the safety signals that had been observed in the phase 3 trial. Clinical trials in Mali and Burkina Faso, showed that in children receiving Seasonal Malaria Chemoprevention (SMC), providing the vaccine just prior to high transmission seasons, matching the period of highest efficacy to the peak transmission season, resulted in substantial reduction in the incidence of clinical malaria and of severe malaria. While SMC has been successfully scaled-up despite the challenges of delivery, there is no established platform for seasonal vaccine delivery and no real-world experience. The objectives of this workshop were, therefore, to share experiences from countries that have introduced the RTS,S vaccine in routine child vaccination programmes, with SMC-implementing countries as they consider malaria vaccine introduction, and to explore implementation strategies in countries with seasonal transmission and where EPI coverage may be low especially in the second year of life. Practical implementation challenges, lessons learned for vaccine introduction, and research questions, towards facilitating the introduction of the RTS,S (and other malaria vaccines) in countries with seasonal malaria transmission were discussed.